Aktivitas Pengguna Taman Tirto Agung Sebagai Ruang Publik - Melisa Grace Girsang; Sariffuddin Sariffuddin (Teknik PWK (Perencanaan Wilayah Kota), 2017)
City is an area that has its high mobility. Urban area as central of political, economic, social as well as culture activity with itself also has certain color over these activities.  The growth of city is influenced by the presence of population growth that support for urban life. Public space is a space that serves activities related to social interaction, increasing income, and art performance (Darmawan, 2009:48). An attractive public space would always be visited by community with different levels of social, economic, ethnic, educational, age difference, and motivations or other interests. The public space which is visited by many communities is downtown park. This park is usually located in the central city that form of green field with shade trees surounding it, or in the form of an urban forest with traditional patterns, or could be with new development designs (Darmawan, 2009:49). Public spaces are complemented with infrastructures for community to interact,  increase quality of life, increase income, and perform art performances. This research purpose to determine the activities of visitor at Taman Tirta Agung as a public space. By knowing visitor activities, it could be seen how the role of park as a public space and the attractiveness on the other activities. This research uses crosstab analysis. Based on the results of field observation has shown that visiting time and age influenced the activity and motivation to visit park.  This research has shown that the recreation and do exercise are dominant to visitor activities at Taman Tirta Agung.  Seeing the high community’s interest toward park that expected for government would be able to improve the facilities and numbers of city park at Semarang.